2023
DOI: 10.59717/j.xinn-med.2023.100042
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to airborne PM<sub>2.5</sub> chemical exposome increases heart rate of middle- and old-aged populations

Yue Sun,
Minghao Wang,
Yanwen Wang
et al.

Abstract: <p>Previous studies have rarely focused on the effects of industrial chemicals on heart rate. There is also a lack of epidemiological investigations to elucidate the mixture effects of complex components of fine particulate matter (PM<sub>2.5</sub>) on cardiovascular health and identify the key toxic components. Here, a population health-oriented methodology is established to quantify mixed effects of airborne PM<sub>2.5</sub> chemical exposome and identify key components. This me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(43 reference statements)
0
1
0
Order By: Relevance
“… 467 The respiratory and cardiovascular systems become the primary targets, with potential consequences ranging from irritations (e.g., coughing) to chronic cardiopulmonary diseases (e.g., hypertension and chronic obstructive pulmonary diseases). 468 , 469 A recent meta-analysis comprising 13 studies showed that higher exposure levels of PFAS, especially for perfluorooctane sulfonic acid (PFOS), perfluorooctanoic acid (PFOA), and perfluorononanoic acid, were significantly associated with a higher risk of hypertension. 470 Notably, particulates with smaller sizes are much more harmful than larger particles because of the longer residence time and greater capacity for deeper penetration in the respiratory tract.…”
Section: Risks Of Ecs To Planetary Healthmentioning
confidence: 99%
“… 467 The respiratory and cardiovascular systems become the primary targets, with potential consequences ranging from irritations (e.g., coughing) to chronic cardiopulmonary diseases (e.g., hypertension and chronic obstructive pulmonary diseases). 468 , 469 A recent meta-analysis comprising 13 studies showed that higher exposure levels of PFAS, especially for perfluorooctane sulfonic acid (PFOS), perfluorooctanoic acid (PFOA), and perfluorononanoic acid, were significantly associated with a higher risk of hypertension. 470 Notably, particulates with smaller sizes are much more harmful than larger particles because of the longer residence time and greater capacity for deeper penetration in the respiratory tract.…”
Section: Risks Of Ecs To Planetary Healthmentioning
confidence: 99%